Increased cancellous bone in the femoral neck of patients with coxarthrosis (hip osteoarthritis): a positive remodeling imbalance favoring bone formation. - Jordan, G; Loveridge, N; Power, J; Clarke, M; Reeve, J (2003)
Osteoporosis is caused by an imbalance between bone resorption and formation which results in an absolute reduction in bone mass. In a previous study we highlighted a condition, osteoarthritis of the hip (coxarthrosis, cOA), where an imbalance between resorption and formation provided beneficial effects in the form of an absolute increase in bone mass. We demonstrated that the femoral neck in patients with cOA had increased cancellous bone area, connectivity and trabecular thickness which might contribute to the protection against fracture associated with the condition. The aim of the present study was to analyze forming and resorbing surfaces in coxarthritic cancellous bone to assess whether increased formation or reduced resorption could be responsible for these structural changes. Whole cross-sectional femoral neck biopsies were obtained from 11 patients with cOA and histomorphometric parameters compared with 14 age- and sex-matched cadaveric controls. The ratio of osteoid surface to bone surface was 121% ( p<0.001) higher in the cases but there was no significant difference in resorptive surface. The percentage osteoid volume to bone volume (%OV/BV; +270%, p<0.001) and osteoid width (O.Wi; +127%, p<0.001) were also higher in the cases. This study suggests that the increased cancellous bone mass seen in cases of cOA is due to increased bone formation rather than decreased bone resorption. Investigation of the cellular and biochemical basis for these changes might provide new insights into the pathogenesis of osteoarthritis and highlight novel biological mechanisms regulating bone multicellular unit (BMU) balance that could be relevant to developing new interventions against hip and other osteoporotic fractures.